The Temple as a Symbol of the Virgin Mary in Medieval Liturgical Hymns and Its Reflection in Images of the Annunciation of the 14th–15th Centuries - José María Salvador-González (Religions)
The current article seeks two interrelated objectives. First, we will shed light on the Mariological and Christological meanings underlying the saying templum Dei and other similar metaphorical expressions, with which countless medieval liturgical hymns, inspired by the Bible, designate the Virgin Mary. Second, we will iconographically interpret some paintings of the Annunciation from the 14th and 15th centuries that represent Mary’s house in Nazareth as a majestic temple. In this order of ideas, we will proceed according to two complementary methodological strategies: first, we will analyze an abundant corpus of fragments of liturgical hymns configured around some biblical metaphors, such as temple of God, tabernacle of the Lord, seat of Wisdom, Ark of the Covenant, temple of Solomon, or throne of the King (Solomon); second, we will analyze eight pictorial Annunciations that include a temple in their scene. The comparison of both analyses, the texts and the images, will allow us to conclude that these texts are the conceptual support of those images, and that the latter are the visual illustrations of those concepts.